The relationship between personality traits and job satisfation among secondary teacher in Putrajaya / Abdullah Khalid Salaudin - Salaudin, Abdullah Khalid (2014)
This research aims to study the Putrajaya secondary school teachers 'personality traits based on 'The Big Five ModeV that might influence their job satisfaction. . In addition, the analysis also showed that these teachers job satisfaction might be strongly affected by their co-workers, promotion, pay and communication. Nature of work, benefit, supervision, reward and operation condition might also be other factors that influenced these teachers satisfaction towards their work The study showed that there were significant relationship between teachersy personality traits and their job satisfactions. The finding of this study illustrated that the overall mean for personality traits was high with the entailing five sub-variables; Agreeableness, Openness, Conscientiousness, Extroversion and Neuroticism The finding of this study would greatly benefit the Ministry of Education (MOE) particularly in planning for better strategies in implementing the Education Development Blueprint 2013 - 2025. Indeed, this study highlighted on the need of MOE and immediate school administrative to constantly provide necessary support and to better understand teachers' personality traits. These might not only motivate teachers but also help them to be satisfied with their jobs.